Kinematics of the hand and key rotation in a tennis forehand drive of tennis players - Pedro, B.; João, F.; Lara, J. P. R.; Veloso, A. P. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of the present study was to quantify kinematic variables of the hand of dominant arm and the main responsible rotation of the upper limb to the racket head velocity in an attack tennis forehand drive. Three elite tennis players and three highperformance tennis players were recorded with inertial measurement units (IMUs) with a frequency of 120 Hz during a cross-court (CC) and an inside-out (IO) forehand drive. The six fastest strokes in both directions were selected for analyses. Differences between two directions were shown in the follow through with a higher wrist abduction when playing in the inside-out direction (cross-court: 13.9 ± 17.2°; inside-out: 16.9 ± 18.6°). Results demonstrated that the horizontal flexion of the upper arm were the main responsible for the racket head velocity (48.1% CC and 45.2% IO).